Effects of Tofogliflozin and Anagliptin Alone or in Combination on Glucose Metabolism and Atherosclerosis-Related Markers in Patients with Type 2 Diabetes Mellitus - Nomura S; Shouzu A; Taniura T; Okuda Y; Omoto S; Suzuki M; Ito T; Toyoda N (Dove Medical Press, 2023)
Shosaku Nomura,1 Akira Shouzu,2 Takehito Taniura,3 Yoshinori Okuda,4 Seitaro Omoto,5 Masahiko Suzuki,6 Tomoki Ito,7 Nagaoki Toyoda8 1Center of Thrombosis and Hemostasis, Kansai Medical University Medical Center, Moriguchi, Japan; 2Division of Diabetes, Saiseikai Izuo Hospital, Osaka, Japan; 3Division of Internal Medicine, Daiwa Hospital, Osaka, Japan; 4Division of Internal Medicine, Meisai Kinen Hospital, Osaka, Japan; 5Division of Internal Medicine, Yukeikai Hospital, Neyagawa, Japan; 6Division of Internal Medicine, Katano Hospital, Katano, Japan; 7First Department of Internal Medicine, Kansai Medical University, Hirakata, Japan; 8Second Department of Internal Medicine, Kansai Medical University, Hirakata, JapanCorrespondence: Shosaku Nomura, Center of Thrombosis and Hemostasis, Kansai Medical University Medical Center, 10-15 Fumizono-cho, Moriguchi, Osaka, 570-8507, Japan, Tel + 81 6 6992 1001, Fax + 81 6 6992 1066, Email shosaku-n@mbp.ocn.ne.jpPurpose: In people with type 2 diabetes mellitus (T2DM), both glucose metabolism abnormalities and atherosclerosis risk are significant concerns. This study aims to investigate the effects of the sodium-glucose cotransporter 2 inhibitor tofogliflozin (TOFO) and the dipeptidyl peptidase-4 inhibitor anagliptin (ANA) on markers of glucose metabolism and atherosclerosis when administered individually or in combination.Methods: Fifty T2DM patients were divided into two groups (receiving either TOFO or ANA monotherapy) and observed for 12 weeks (observation points: 0 and 12 weeks). The TOFO and ANA groups were then further treated with ANA and TOFO, respectively, and the patients were observed for an additional 36 weeks (observation points: 24 and 48 weeks). Therapeutic effects and various biomarkers were compared between the two groups at the observation points.Results: Combination therapy led to significant improvements in HbA1c levels and atherosclerosis markers. Additionally, the TOFO pretreatment group exhibited significant reductions in sLOX-1 and IL-6 levels.Conclusion: The increase in sLOX-1 and IL-6 levels, which indicates the response of scavenger receptors to oxidized low-density lipoproteins in people with T2DM, is mitigated following TOFO and ANA combination therapy. TOFO alone or in combination with ANA may be beneficial for preventing atherosclerosis development in people with T2DM, in addition to its effect on improving HbA1c levels.Keywords: tofogliflozin, anagliptin, type 2 diabetes mellitus, atherosclerosis, soluble LOX-1